Decreased Serum T3 after an Exercise Session is Independent of Glucocorticoid Peak - Neto, R. A. L.; de Souza dos Santos, M. C.; Rangel, I. F.; Ribeiro, M. B.; Cavalcanti-de-Albuquerque, J. P. A.; Ferreira, A. C. F.; Cameron, L. C.; Carvalho, D. P.; Werneck de Castro, J. P. S. (Hormone and Metabolic Research, 2013)
Physical exercise increases serum glucocorticoids, which is believed to be involved in the fall of T3 after high intensity exercise. The objective was to evaluate whether a physical exercise session alters the thyroid economy and adrenal axis in humans, and the possible role of corticosteroids in thyroid function disturbance. Active but not athlete subjects were enrolled in an open field competition and cortisol, TSH, T3, and T4 were measured before and after the race. To give new insights into the mechanisms underlying the changes in thyroid economy after exercise, we used a rat model to evaluate the impact of blocking corticosterone synthesis during treadmill exercise by metyrapone administration. Cortisol levels increased 1.5-fold (from 28.2±3.8 to 42.2±2.2 μg/dl; p<0.05), while serum T3 decreased by 13% (from 115±5 to 99±5 μg/dl; p<0.05) 6 h after the race in humans. Also, in rats, glucocorticoid increased by 2-fold while T3 decreased 15% after exercise session (p<0.05). However, the complete blockage of corticosterone peak did not impair serum T3 decrease observed in rats submitted to exercise. Interestingly, the lack of corticosterone peak led not only to lower serum T3, but also to decreased serum T4, indicating that corticosterone might be fundamental for the maintenance of serum thyroid hormone levels after high intensity exercise. Although cortisol increases and T3 decreases after high intensity exercise in both humans and rats, it does not seem to be a cause-effect response since pharmacological blockage of corticosterone peak does not modulate T3 response.
Keywords: thyroid hormones; deiodinase; glucocorticoids; high intensity exercise